GRAVES DISEASE IN CHILDREN AND ADOLESCENTS: PROGRESSION FROM HYPERTHYROIDISM TO SPONTANEOUS HYPOTHYROIDISM - G, Farizan; Wong, Jeanne SL; Selveindran, Nalini M; Hong, Janet YH (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Graves’ disease (GD) is an autoimmune disorder characterized by hyperthyroidism caused by the presence of thyroid stimulating-antibody. In adult patients with GD, approximately 5-20% of patients eventually progress to hypothyroidism after a period of remission of more than 10 years. Possible mechanisms for the development of spontaneous hypothyroidism are the development of TSH-blocking antibodies or a chronic autoimmune process similar to Hashimoto thyroiditis. In children, whether a subset of patients’ progress to hypothyroidism is unclear. RESULTS We present three cases of pediatrics GD who progress from hyperthyroidism to hypothyroidism. Case 1: 17-year-old girl. Treated with carbimazole for 6 years. Defaulted follow up for 1 year, self-prescribed carbimazole. Severely hypothyroidism when re-presented (FT4 3.7 pmol/, TSH 179.9 mIU/L). Currently on L-thyroxine 100 mcg daily past 1 year. At presentation TRAb 28.1 U/L (<1), Anti-TG >4000 U/ml (<1), Anti-TPO >929 U/ml (<1). At remission TSI 120 IU/L (<0.55), anti-TG 1313 U/ml(<1), anti-TPO >972 U/ml(<1) Case 2: 11-year-old girl. Treated with carbimazole 3 years. Developed subclinical hypothyroidism (FT4 8.4 pmol/L and TSH 7.455 mIU/mL) after 1 year of remission. Spontaneous normalization of TFT after 2 months currently euthyroid. At presentation TRAb 20 U/L (<1), Anti-TG 1425 U/ml, Anti-TPO >986 U/ml.At remission:TRAb 0.46IU/L(<1) Case 3: 10-year-old girl presented at age of 8 years with weight loss over 4 months. Treated with carbimazole for 1 year. Developed hypothyroidism (FT4 8.9 pmol/L, TSH 13.45 mIU/mL) after 8 months of remission. Currently on L-thyroxine 25 mcg for duration of 3 months. At presentation TRAb 151 IU/L (N<0.55), Anti-TG 408.9U/ml (n<1), Anti-TPO>988 U/ml (N <1). At remission,TRAb 24.2 IU/L(<1),Anti-TG:507 U/ml,Anti-TPO: >986 U/ml. CONCLUSION Our cases demonstrate that there are a proportion of children with GD in remission that develop spontaneous hypothyroidism. Highly elevated levels of anti-TPO could be a predictive risk factor for this.